The use of crossword accounting puzzle to enrich the English vocabulary of the students of SMK Negeri Temayang, Bojonegoro - Prastiwi, Chyntia Heru Woro; Tirtanawati, Meiga Ratih; Sholehuddin, Muhammad (Universitas Muhammadiyah Magelang, 2021)
Graduates of the accounting vocational High School need mastery of English in order to have a competitive advantage and be ready to enter the world of work. However, so far, learning English in the Accounting class at SMK Negeri Temayang, Bojonegoro is still focused on general skills that are not in accordance with the needs of the world of work. As a result, students do not understand foreign terms contained in financial statements. This service activity aims to increase English vocabulary through crossword accounting puzzles in the form of games and designs. By actively engaging in crossword games and designing their own English puzzles for accounting using free online tools, students can enrich their English vocabulary in Accounting. At the end of this service activity, 16 accounting puzzles were produced that can be used as English learning media.